A simple and cost-effective bidirectional antenna using a probe excited circular ring - Kosulvit, Sompol; Krairiksh, Monai; Phongcharoenpanich, Chuwong; Wakabayashi, Toshio (My University, 2001)
This paper presents a simple and cost-effective bidirectional antenna using a probe excited circular ring. The structure of the antenna is simple i.e., a linear electric probe surrounded by the circular ring. The principle of the antenna design is easy and straightforward. A choice of the ring radius is first chosen to achieve the condition that only the dominant mode can be propagated. Furthermore, it is found that for a specific ring radius, the radiation patterns of the antenna are varied as the ring width. Then, the optimum ring width that provides the maximum directivity is determined. The criterion of the selection of the ring width for various ring radii is illustrated as the guidelines for the antenna design. The fabricated antennas at the operating frequency of 1.9065 GHz are measured and compared with the theoretical predictions. It is apparent that these results are in reasonable agreement. The bidirectional pattern with the gain of 5.4 dBi over the bandwidth of 17% is obtained. Moreover, the antenna can be easily fabricated with the low production cost. Therefore, this antenna is suitable for installing at the base station in the street cell.
Keywords: Base station antenna; Bidirectional antenna; Circular ring; Mobile antenna; Probe